Colloidal Nanoparticles Used as Anticancer Drug Carriers - Zhivkov , Alexandar M.; Hristova , Svetlana H.; Popov , Trifon T. (Advanced Concepts in Pharmaceutical Research Vol. 1, 2023)
Cancer is a socially significant disease, since the incidence of oncological diseases is continuously growing worldwide. This necessitates the search for alternative therapeutic strategies beyond traditional chemo- and radiotherapy to reduce adverse effects, in particular high toxicity. Molecular chemotherapeutics have cytotoxic effects on both cancer cells and healthy dividing cells, in particular those of the immune system. The main problem of chemotherapy, selectivity, can be solved by using some distinctions of cancer cells from healthy cells. One such difference is their ability to phagocytose colloidal particles of submicron size. For this purpose, it is necessary to construct carrier particles through which molecular chemotherapeutics can be delivered and released inside the cancer cell.. Chemotherapeutic agents can be carried by nanoparticles, hydrogels, composed nanoparticle-hydrogels, micelles and liposomes. In this way, to achieve high transport efficiency, uptake and selectivity composite particles should be prepared starting from their physicochemical properties. The main focus of this book chapter is given to the surface properties as hydrophilicity/hydrophobicity and electric charge of nanoparticles formed from metal and dielectric substances: metals (gold, silver), metal-oxides of iron, aluminum, titanium and zirconium, silicates (quartz), alumosilicates (montmorillonite, kaolinite), and carbonates. The physicochemical properties of the nanoparticles are emphasized in order to assist researchers in choosing appropriate nanoparticles for adsorption of drugs with hydrophilic and hydrophobic organic molecules in order to synthesize composite particles for using as carriers of different anticancer agents.